Cultural influences on spontaneous trait inferences - Moreira, Ana Isabel Alves (2018)
This work explores the effect of culture in the inference of personality traits from people’s behaviours (spontaneous trait inference - STI). Specifically, it explores the effect of the individualism/collectivism cultural dimension. In Study 1 we manipulated the independent/interdependent self-construal to explore whether it would mimic the differences found between individualistic and collectivistic cultures. Study 2 explored the impact of the horizontality/verticality distinction of individualism/collectivism. Shimizu, Lee, and Uleman’s (2017) adaptation of the false recognition paradigm was used in both studies to measure STIs. Despite independents making more STIs on average than interdependents, as theoretically expected, Study 1 fell short of statistical significance possibly due to having a small sample size. Study 2 was unable to find a statistically significant difference between horizontal individualists (HI) and horizontal collectivists (HC) on STI. We discuss the relevance of these null results and their implications in the context of STI differences between individualists and collectivists.